STUDIES OF PHOTONUCLEAR REACTIONS AND PHOTON ACTIVATION ANALYSIS IN THE GIANT DIPOLE RESONANCE REGION USING MICROTRONS - THIEP, TRAN DUC; DO, NGUYEN VAN; THI, NGUYEN KHAC; AN, TRUONG THI; SON, NGUYEN NGOC (Communications in Physics, 2007)
Mictrorons are accelerators of electrons and are simultaneous sources of bremsstrahlung photon flux and fission neutrons. In 1982, a microtron of seventeen trajectories Microtron MT - 17 was put into operation at the National Institute of Physics of Vietnam. Though very modest, microtons are very useful for developing countries such as Vietnam in both fundamental and applied physics research. During the recent years by using the above mentioned MT - 17 and microtrons from other institutes we have carried out different investigations. In this report we present some results obtained in the studies of photonuclear reactions and photon activation analysis in the giant dipole resonance region.